2018
DOI: 10.3390/ijms19071972
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Human β-Glucocerebrosidase in Nicotiana benthamiana Root Culture

Abstract: Gaucher disease is caused by a deficiency of the enzyme glucocerebrosidase (GCase). Currently, enzyme-replacement therapy using recombinant GCase produced in mammalian cells is considered the most effective treatment. Plants are an attractive alternative host for recombinant protein production due to the low cost of large-scale production and lack of risk of contamination by human pathogens. Compared to whole plants, root cultures can grow faster. Therefore, this study aimed to produce recombinant GCase in a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(56 reference statements)
1
9
1
Order By: Relevance
“…This enzyme is also related to plant physiology, including cell wall degradation and to the activation of both phytohormones and chemical compounds (Morant et al, 2008;Pankoke et al, 2013). Internal βglucosidases were also reported previously (Naphatsamon et al, 2018). Our results indicated that this system has the potential to be competitive for recombinant GCase production with high levels of biological activity.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This enzyme is also related to plant physiology, including cell wall degradation and to the activation of both phytohormones and chemical compounds (Morant et al, 2008;Pankoke et al, 2013). Internal βglucosidases were also reported previously (Naphatsamon et al, 2018). Our results indicated that this system has the potential to be competitive for recombinant GCase production with high levels of biological activity.…”
Section: Discussionsupporting
confidence: 82%
“…M, PageRuler TM protein ladder; Crude, crude protein; Purified GCase, purified GCase from Phenyl 650M elution fractions 6 (E6); +, Cerezyme ® . studies: 65.5 U/mg TSP (Limkul et al, 2016), 24 U/mg TSP (He et al, 2012), 44.5 U/mg TSP (Limkul et al, 2015), and 81.4 U/mg TSP (Naphatsamon et al, 2018). On the other hand, the low GCase activity observed in the negative control was attributed to internal β-glucosidases produced in plants, which plays important roles in plant defense systems.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, hairy roots of many different plant species have been utilized to produce various both secondary metabolites and recombinant proteins of pharmaceutical value at varying yields, such as enzymes (Woods et al., 2008), vaccines and hormones (Woffenden et al., 2008; Skarjinskaia et al., 2013), antibodies in different formats (Wongsamuth and Doran, 1997; Lonoce et al., 2016, 2018). Production of enzymes for replacement therapy of rare diseases was also reported (Rodriguez-Hernandez et al., submitted; Naphatsamon et al., 2018). Recombinant proteins produced in engineered hairy root cultures can be also secreted in the culture medium simplifying downstream purification processes (Guillon et al., 2006; Häkkinen et al., 2014).…”
Section: Introductionmentioning
confidence: 91%
“…The produced enzyme in the latter case does not contain any targeting signal to the vacuole. Active GBA has recently also been produced in root cultures of Nicotiana tobacco (Naphatsamon et al, 2018). Finally, GBA enzyme with high mannose N-glycans (gnt1-GBA) was produced in mutant rice (Jung et al, 2019).…”
Section: Lysosomal Enzymes and Their Production In Plantsmentioning
confidence: 99%